Al-mahārāt al-Asāsiyyah li al-Tarjamah (Suatu Kajian Teoritis Tantang Keterampilan Dasar Penerjemah) - Cutri A Tjalau (‘A Jamiy : Jurnal Bahasa dan Sastra Arab, 2022)
The translation is an effort to replace the source language text material with equivalent and appropriate material in the target language. Current developments and advances in science and technology have implications for the need for reliable translators. This study will describe and describe in simple terms what competencies a translator must-have. This research is library research with a descriptive method. The research data are sourced from books on the theory of tarjamah, and scientific articles related to translation. The results of the study indicate that a translator must have the following skills; 1) master the source language and target language well, 2) master the translation methods, techniques, strategies, and procedures, 3) master the material or field of science from the translated text.